Feasibility and safety of radical prostatectomy for oligo‐metastatic prostate cancer: the Testing Radical prostatectomy in men with prostate cancer and oligo‐Metastases to the bone (TRoMbone) trial. (27th January 2022) - Sooriakumaran, Prasanna; Wilson, Caroline; Rombach, Ines; Hassanali, Neelam; Aning, Jonathan; D. Lamb, Alastair; Cathcart, Paul; Eden, Christopher; Ahmad, Imran; Rajan, Prabhakar; Sridhar, Ashwin; Bryant, Richard J.; et al.
Abstract : Objectives: To test the feasibility of randomisation to radical prostatectomy (RP) plus pelvic lymphadenectomy in addition to standard‐of‐care (SOC) systemic therapy in men with newly diagnosed oligo‐metastatic prostate cancer. Patients and Methods: A prospective, randomised, non‐blinded, feasibility clinical trial with an embedded QuinteT Recruitment Intervention (QRI) to optimise recruitment was conducted in nine nationwide tertiary care centres undertaking high‐volume robotic surgery. We aimed to randomise 50 men with synchronous oligo‐metastatic prostate cancer within an 18‐month recruitment period to SOC systemic therapy vs SOC plus RP (intervention arm). The main outcome measures were: ability to randomise patients, optimised by a QRI; EuroQoL five Dimensions five Levels (EQ‐5D‐5L) questionnaires to capture quality‐of‐life (QoL) data at baseline and 3 months post‐randomisation; routine clinicopathological assessment to capture adverse events and prostate‐specific antigen in both arms, plus standard perioperative parameters in the surgical arm. Results: A total of 51 men were randomised within 14 months (one was subsequently deemed ineligible), with 60–83% accrual rate in centres that recruited at least two patients. All patients completed the trial follow‐up; one patient in the intervention arm subsequently did not undergo the surgical intervention and one in the SOC arm refused all therapies. The QRI positively impacted recruitment. QoL data showed similarly high functioning in both study arms. Surgery for men with oligo‐metastatic prostate cancer was found to be safe and had similar impact on early functional outcomes as surgery for standard indication. Conclusion: It is feasible to randomise men with synchronous oligo‐metastatic prostate cancer to a surgical intervention in addition to standard systemic therapies. While surgery appeared safe with no substantial impact on QoL in this feasibility study, a large randomised controlled trial is now warranted to examine treatment effectiveness of this additional component in the multimodality management of oligo‐metastatic prostate cancer.